2015
DOI: 10.1007/s00167-015-3602-z
|View full text |Cite
|
Sign up to set email alerts
|

Distal femoral varus osteotomy for unloading valgus knee malalignment: a biomechanical analysis

Abstract: Progressive unloading of the lateral tibiofemoral compartment occurred with increasing DFVO correction angles. Clinically, when performing a DFVO for valgus malalignment, surgeons should consider overcorrecting the osteotomy by 5° to restore near-normal contact pressures and contact areas in the lateral compartment rather than the traditional teaching of correcting to neutral alignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 28 publications
1
32
0
1
Order By: Relevance
“…The joint was loaded to 500 N along the tibial axis at all flexion angles. 17 In each case, the joint load was increased linearly to 500 N over 15 seconds (33 N/s), held for 5 seconds, and unloaded at 50 N/s. The 500-N load magnitude was chosen after prior pilot studies indicated that the joint contact pattern and location of peak pressure were equivalent to those achieved at higher loads but without saturation of the pressure magnitude within discrete sensor elements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The joint was loaded to 500 N along the tibial axis at all flexion angles. 17 In each case, the joint load was increased linearly to 500 N over 15 seconds (33 N/s), held for 5 seconds, and unloaded at 50 N/s. The 500-N load magnitude was chosen after prior pilot studies indicated that the joint contact pattern and location of peak pressure were equivalent to those achieved at higher loads but without saturation of the pressure magnitude within discrete sensor elements.…”
Section: Methodsmentioning
confidence: 99%
“…Little is known about the biomechanical changes in the knee joint caused by DFO. A recent study by Quirno et al 17 simulated a 10° valgus load in cadaveric specimens in full extension and then sequentially performed 5°, 10°, and 15° distal femoral varus osteotomy. They found that 10° DFO equalized the medial and lateral tibiofemoral contact pressures in full extension and that 15° DFO shifted weightbearing to the medial compartment, effectively unloading the lateral compartment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Quirno et al, in a recent biomechanical analysis, reported that over-correcting valgus deformity better unload the lateral compartment and better restore the normal biomechanics compared to correction to neutral alignment. The authors concluded that overcorrecting the osteotomy of 5° normalize contact pressure and contact areas in the lateral compartment (23). Similarly, others authors reported good clinical outcomes with valgus deformity over-correction (mechanical axis goal at 40-41% of tibial plateau) due to lateral compartment unloading and medial muscles' forces neutralization (20,24).…”
Section: Preoperative Settingmentioning
confidence: 88%
“…1 Distal femoral varus osteotomy (DFVO) can effectively correct valgus knee malalignment and unload the lateral compartment. 2 In fact, biomechanical analysis has demonstrated that the elevated contact pressures seen in the lateral compartment with valgus malalignment are normalized with corrective DFVO. 2 Good to excellent clinical results in nonathletes with symptomatic lateral compartment gonarthrosis have been reported with both medial closing wedge [3][4][5][6][7][8][9][10][11][12][13][14][15][16] and lateral opening wedge [17][18][19][20][21][22] DFVO.…”
Section: Introductionmentioning
confidence: 99%